(untitled) (Journal of Dhaka Medical College, 2010)
Blood serves as a vehicle for transmission of blood-borne pathogens and transfusion-associated malaria is a potentially serious complication. The present study was conducted to determine the prevalence of Malaria parasites in blood donors. Total of 400 blood donors were selected from Transfusion Medicine Department of two teaching institutes, Bangabandhu Sheikh Mujib Medical University (BSMMU) and National Institute of Diseases of Chest and Hospital (NIDCH), Dhaka between the period of 1st January and 30th April 2003. The blood samples were examined under microscope by thick film in the laboratory of Institute of Epidemiology, Disease Control & Research (IEDCR), Dhaka. The socio-demographic characteristics of the study subjects show that 304 (76%) blood donors were males and 96 (24%) of them were females. The malaria parasites were found in 3 (0.76%) donors out of 400 donors. From 400 donors, 52 (13%) donors had the history of residence/ travel in malaria zone and 348 (87%) had no such history. The 8 (15%) out of 52 who had the history of residence/ travel in malaria zone had previous history of malaria and had taken anti-malarial drug. It can be concluded from the present study that there is some risk of transmission of malaria parasites in blood transfusion among the voluntary and professional blood donors in Bangladesh. Key words: Malaria parasites; Blood donors; Thick film. DOI: 10.3329/jdmc.v17i2.6590 J Dhaka Med Coll. 2008; 17(2) : 94-97